2009
DOI: 10.1007/s00244-009-9390-z
|View full text |Cite
|
Sign up to set email alerts
|

Larval Responses of Three Midwestern Anurans to Chronic, Low-Dose Exposures of Four Herbicides

Abstract: Low levels of agricultural herbicides often contaminate surface water and might persist throughout the growing season, potentially acting as stressors on aquatic organisms. Although low-dose, chronic exposures to agrochemicals are likely common for many nontarget organisms, studies addressing these effects using end-use herbicide formulations are rare. We exposed three common species of tadpoles to conservative levels of atrazine, S-metolachlor, and glyphosate end-use herbicide formulations throughout the larv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(52 citation statements)
references
References 44 publications
2
48
2
Order By: Relevance
“…Exposure to ecologically relevant levels of atrazine may produce effects ranging from multiple gonads and demasculinization in male frogs to increased disease and parasite sensitivity in amphibians (Hayes et al, 2002a;Forsen and Storfer, 2006). Williams and Semlitsch (2009) reported that low-dose exposures to atrazine and metolachlor did not result in a significant increase in larval mortality in three species of anurans but noted that combinations of commonly used pesticides have elicited negative effects in some studies (Hayes et al, 2006;Relyea, 2009). Metolachlor and several other industrial chemicals have been detected in two Missouri rivers containing Ozark hellbenders (Cryptobranchus alleganiensis bishopi), but the effects of these exposures have not been studied (Solis et al, 2007b).…”
Section: Water Qualitymentioning
confidence: 99%
“…Exposure to ecologically relevant levels of atrazine may produce effects ranging from multiple gonads and demasculinization in male frogs to increased disease and parasite sensitivity in amphibians (Hayes et al, 2002a;Forsen and Storfer, 2006). Williams and Semlitsch (2009) reported that low-dose exposures to atrazine and metolachlor did not result in a significant increase in larval mortality in three species of anurans but noted that combinations of commonly used pesticides have elicited negative effects in some studies (Hayes et al, 2006;Relyea, 2009). Metolachlor and several other industrial chemicals have been detected in two Missouri rivers containing Ozark hellbenders (Cryptobranchus alleganiensis bishopi), but the effects of these exposures have not been studied (Solis et al, 2007b).…”
Section: Water Qualitymentioning
confidence: 99%
“…Exposure to low levels (700 ppb) of the glyphosate herbicide roundup WeatherMax (Monsanto Canada inc., Winnipeg, Manitoba) resulted in 80% mortality of Boreal Chorus Frog tadpoles (Williams and Semlitsch 2010). The high mortality rate is likely a result of the unique surfactant in the product, as roundup Original (Monsanto Canada inc.) did not cause high levels of mortality (Williams and Semlitsch 2010). however, roundup WeatherMax was not available in Canada until the early 2000s, and the Boreal Chorus Frog was declining before that (e.g., Daigle 1997), so it likely does not explain the declines.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, pesticides may interact with other stressors such as predators Mills 2001, Boone andJames 2003). All this applies to many pesticides, but some non-selective herbicides seem to be amongst the most dangerous for amphibians (see Williams and Semlitsch 2010).…”
Section: Indirect Potential Effects Of Gmos On Anuran Amphibiansmentioning
confidence: 99%